Peran Strategis Dinas Perpustakaan Kabupaten Aceh Tenggara Dalam Mendorong Minat Baca - Al Muqtafi, Muhafidz; Irwansyah, Irwansyah; Faturrahman, Muslih (UPT Perpustakaan Universitas Bengkulu, 2025)
ABSTRACT This study aims to explore the strategies of the Aceh Tenggara Regency Library Service in increasing reading interest among the community, particularly among the youth, using a qualitative method. The study involves in-depth interviews with the head librarian and library staff. The findings indicate that the main strategies implemented include diversification of reading materials, intensive literacy campaigns, and the utilization of digital technology through the 'Perpus Agara' application. Diversification of reading materials is achieved by enriching the collection of books and digital materials that are relevant and appealing to various age groups and interests. Literacy campaigns are conducted through various activities such as workshops, book clubs, and outreach to schools. Meanwhile, the 'Perpus Agara' application facilitates digital access to library materials and has been downloaded by over 1,000 users. Although these strategies show an increase in reading interest, several challenges remain, including budget constraints, a lack of skilled human resources, and difficulties in reaching remote communities. Additionally, low literacy levels among parents and a lack of support from schools also pose obstacles. To address these challenges, it is recommended that the Library Service enhance collaboration with various parties, including local government, educational institutions, and non-governmental organizations, to secure additional support in the form of funding and expertise. Furthermore, ongoing training for library staff and the development of more innovative literacy programs tailored to local needs are necessary. Optimizing the use of technology and social media can also be an effective tool in increasing reading interest and disseminating information about library programs. Keyword : Library strategy, reading interest, library challenges